Automobile mechanical and electrical systems automotive technology : vehicle maintenance and repair - Denton, Tom (Butterworth-Heinemann/Elsevier, 2011)
Learn all the theory and practical skills you need to pass the national level 2 Vehicle Maintenance and Repair courses from City and Guilds, IMI and BTEC. 'Automobile Mechanical Systems' explains in detail how different mechanical systems work, how to diagnose faults and how to repair them.